Activity Workstations in High Schools: Decreasing Sedentary Behavior Without Negatively Impacting Schoolwork - Pilcher, June J.; Hulett, Timothy L.; Harrill, Paige S.; Cashman, Jessie M.; Hamilton, G. Lawson; Diaz, Eva (Frontiers in Psychology, 2022)
High school students are at risk for increased sedentary behavior due in part to a decrease in physical activity throughout adolescence and to required sedentary behavior during much of the school day. The purpose of the current study is to examine the impact of using activity workstations in a high school English class for struggling readers. Twenty high school students participated in the study. The participants completed a 16-week study where each participant used an activity workstation for 8 weeks and a traditional desk for 8 weeks in a crossover design for a 40-min period during normal class. They responded to a series of subjective questions about reading and schoolwork at the beginning and end of each 8-week session and followed the READ 180 program designed to help struggling readers during the study. The results indicated that academic performance increased in both desk conditions during the study and from the beginning to the end of the study. In addition, there was a significant improvement in items in the subjective survey related to reading, motivation, and schoolwork in both desk conditions across the study. The current results suggest that using an activity workstation in the classroom did not negatively affect academic performance or students’ perceptions of working on academic assignments compared to the traditional desk condition. These results indicate that activity workstations could be implemented in classrooms to provide students with a non-sedentary option during the school day thus increasing physical activity in students.